Dispute resolution methods in the construction industry - Dorothy, Chai Sin Yee (Universiti Malaysia Sarawak, UNIMAS, 2005)
Both Litigation and Arbitration are traditional dispute resolution methods available in our construction industry. Parties in dispute are allowed to opt for litigation as means of dispute resolution unless there is consent and agreement between the parties to resolve their disputes by arbitration. This study will compare both the methods in term of their similarities and differences of their rules and procedures and to draw out their advantages and disadvantages of each method. This study then seeks to determine the suitability and the effectiveness of each method in resolving engineering and construction cases.